2018
DOI: 10.1177/0890334418767832
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Beliefs and Distress in Pregnancy and Postpartum With Breastfeeding Initiation and Early Cessation

Abstract: Prenatal beliefs about breastfeeding, pregnancy-specific distress in early pregnancy, and general anxiety and depressive symptoms in postpartum are associated with breastfeeding initiation and continuation. Of clinical relevance, addressing prenatal and postpartum distress in the implementation of breastfeeding practice interventions could improve breastfeeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…Mothers who do not meet their breastfeeding goals can feel sadness, depression, embarrassment, and guilt (Demirci et al, 2018), negatively affecting their mental health. Conversely, a mother's mental health also affects her duration of any breastfeeding (Ritchie-Ewing et al, 2019). Mothers who stop breastfeeding may need support from many sources (Jackson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who do not meet their breastfeeding goals can feel sadness, depression, embarrassment, and guilt (Demirci et al, 2018), negatively affecting their mental health. Conversely, a mother's mental health also affects her duration of any breastfeeding (Ritchie-Ewing et al, 2019). Mothers who stop breastfeeding may need support from many sources (Jackson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-related stress, generalized anxiety, and postpartum depression have been found to decrease initiation and continued breastfeeding. 39 Studies of lowincome women found that stressful life events, in particular financial stressors, were associated with shorter breastfeeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum anxiety and depressive symptoms have been found to be associated with breastfeeding, mother-child emotional bonding and interaction, which may affect the health and development of infants (23,27). During the COVID-19 outbreak, a variety of factors may have influenced the postnatal mental health of mothers with COVID-19, such as long-term home quarantine, infections during pregnancy, and prolonged mother-child separation.…”
Section: Postpartum Anxiety and Depression Among Mothers During Covid-19 Pandemicmentioning
confidence: 99%